2015
DOI: 10.1155/2015/175436
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled Discontinuation of Long-Term Acid-Suppressant Therapy: A Randomised Trial in General Practice

Abstract: Objective. To investigate whether patients on long-term antisecretory medication need to continue treatment to control symptoms. Methods. A double-blinded randomised placebo-controlled trial in general practices in Denmark. Patients aged 18–90 who were treated with antisecretory drugs on a long-term basis were randomized to esomeprazole 40 mg or identical placebo. Outcome measures were time to discontinuation with trial medication due to failed symptom control analysed as survival data. The proportion of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Furthermore, up to one third of longterm PPI users have been shown not to have undergone upper endoscopy to confirm presence of erosive esophagitis [Lassen et al 2004], making the indication for long-term treatment doubtful. However, getting such patients off PPI has proven difficult [Batuwitage et al 2007;Reimer and Bytzer, 2010;Ahrens et al 2012;Wermeling et al 2014;Zwisler et al 2015], and this could, at least in part, be a reason for the prevalence of use observed in our study. One possible reason for continuing PPI use in patients without a well established indication could be rebound-acid hypersecretion, that is, acid hypersecretion following withdrawal of PPI therapy.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, up to one third of longterm PPI users have been shown not to have undergone upper endoscopy to confirm presence of erosive esophagitis [Lassen et al 2004], making the indication for long-term treatment doubtful. However, getting such patients off PPI has proven difficult [Batuwitage et al 2007;Reimer and Bytzer, 2010;Ahrens et al 2012;Wermeling et al 2014;Zwisler et al 2015], and this could, at least in part, be a reason for the prevalence of use observed in our study. One possible reason for continuing PPI use in patients without a well established indication could be rebound-acid hypersecretion, that is, acid hypersecretion following withdrawal of PPI therapy.…”
Section: Discussionmentioning
confidence: 82%
“…Finally, the study had a short follow-up period of only 8 weeks. Although previous studies found that asymptomatic patients often experienced heartburn, acid regurgitation, and dyspepsia during the first 4 to 8 weeks after PPI discontinuation, 21,22,24,33 there is a possibility that participants in the current study experienced return of GERD symptoms after the study ended.…”
Section: Limitationsmentioning
confidence: 73%
“…Previous studies, which reported discontinuation success rates of only 14% to 64%, were conducted in primary care or community patients. [21][22][23][24][25] In contrast, the current study focused on a residential care site, and the mean age of the study population was 80 years, older than the mean age in previous studies. Previous studies found that it was easier to discontinue PPIs in older patients because their GERD symptoms were subjectively less severe than those of younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Most studies were conducted in Europe (n = 13) and the US (n = 8), with two studies from Taiwan, one study from Canada, one from Australia, one from Brazil, and one from South Korea. Eleven studies were conducted in general practices or in outpatient clinics, 16,18,[22][23][24][25][26][27][28][29][30] five in nursing homes, 19,[31][32][33][34] three were done in hospitals as well as individual physician practices 17,35,36 and one was conducted in a palliative care setting. 37 The other papers did not specify the setting of the study 20,21,[38][39][40][41] (further details are available from the authors on request).…”
Section: Characteristics Of Selected Publicationsmentioning
confidence: 99%